Digital Capabilities and Sustainable Competitive Advantages: The Case of Emerging Market Manufacturing SMEs - Dinh Van Hoang; Nguyen Thi Hien; Han Van Thang; Phan Nguyen Truc Phuong; Trang Thi-Thuy Duong (SAGE Open)
This study investigates the impact of digital capabilities on sustainable competitive advantages among manufacturing small and medium-sized enterprises (SMEs) in Vietnam, an emerging market, through the lens of the dynamic capabilities view. The research examines the mediating role of digital absorptive capacity and the active role of digital leadership in this relationship. The research used both qualitative and quantitative research, in which a two-stage quantitative approach was employed, using partial least squares-structural equation modeling (PLS-SEM) and artificial neural network (ANN) on data collected from 314 firms. The results reveal a positive correlation between digital capabilities and sustainable competitive advantages, with digital absorptive capacity acting as a positive mediator. The study also found positive relationships between digital capabilities and digital absorptive capacity, as well as between digital absorptive capacity and sustainable competitive advantages. Digital leadership was identified as an active factor positively affecting digital capabilities, digital absorptive capacity, and sustainable competitive advantages, with digital capabilities playing a positive mediating role in these relationships. By exploring the roles of digital absorptive capacity and digital leadership, this study offers novel contributions to understanding a firm’s digital capabilities and sustainable competitive advantages. The findings provide practical implications for managers of emerging market manufacturing SMEs, such as those in Vietnam, who aim to enhance sustainable competitive advantages by leveraging digital capabilities.